Analisi Daya Dukung Pondasi Jembatan (Studi Kasus : Jembatan W10 Kota Pagar Alam) - M.Sang Gumilar; Bobi Bobi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
This study aims to see the stability of the bearing capacity towards the Shear, Bolt, Landslide on the bridge. From the results of the study, the bridge obtained a total weight of 85251.8 kg / m ^ ҆ 85.25 Ton / m 'with' Soil Cohesion 10 kg / cm2 ∂ Soil 17.9 kg / cm2 Active soil coefficient 0.40 kg / m2 stability against 2.84> 1.5 shear safe against ground shear force. The rolling factor with a value of 1.9> 1.5 is safe against rolling forces, the slope of the bearing capacity is 4.55> 2.5 safe against landslides.